Pengaruh Mata Kuliah Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Ekonomi - Bella Nova Dhira; Rinto Alexandro; Windy Utami Putri (FKIP, Universitas Palangka Raya, 2021)
The Economic Education Study Program at the University of Palangka Raya is one of the majors that has implemented entrepreneurship education. Entrepreneurship education has been included in the curriculum and has become a compulsory subject for economic education students. The purpose of this study was to determine whether there was an effect of entrepreneurship courses on the interest of students of Economic Education Class of 2017 at the University of Palangka Raya and to determine the interest in entrepreneurship of students of Economic Education of Class of 2017 at the University of Palangka Raya. In conducting this research, quantitative methods were used, while data collection was carried out by analyzing data and submitting a questionnaire/questionnaire to Economic Education students class 2017 at the University of Palangka Raya. The population in this study were students of economic education class 2017 at the University of Palangka Raya and the sample used was total sampling where all members/elements of the population were investigated. The validity test was carried out through the calculation of SPSS for windows while the reliability test used the Cronbach's alpha formula. The data analysis technique used (1) validity and reliability tests, (2) hypothesis testing, namely (a) simple linear regression, (b) partial t-test, and (c) coefficient of determination R^2. From the results of the Simple Linear Regression Test, Y = 18.689 + 0.677. X, with the coefficient of determination or KP: 0.370, it means that the entrepreneurship course variable contributes to the interest in entrepreneurship (Y) by 37%. While the remaining 63% is influenced by other factors outside the variables in the study. The results of the t-value test show that the t_count value is 4.529 > t_table, which is 2.03011 with a significant level of 0.000. The significant level is smaller than 0.05 which means that the hypothesis in this study rejects Ho and accepts Ha. Thus it can mean that the hypothesis